Banking litigation - Warne, David (Sweet & Maxwell, 2005)
The new edition of this respected work guides practitioners through the wide range of issues relevant to banking litigation. It covers the major areas of potential conflict, from disputes with domestic customers to those arising from global custodianship and international banking. Procedural advice is given alongside more strategic considerations, helping practitioners respond effectively at all stages of a dispute. The text has been extensively updated to provide full coverage of recent legislation - such as the FSMA 2000, the Human Rights Act 1998, the Data Protection Act 1998, Contracts (Rights of Third Parties) Act 1999 and the Electronic Communications Act 2000 - as well as changes to the Banking Code of Practice, and the FSA Ombudsman. There is a new chapter devoted to the regulatory regime under the Financial Services and Markets Act 2000; while the money laundering section has been completely revised in light of the Proceeds of Crime Act 2002. * An authoritative, high-level treatment of banking litigation that has been cited in court * Deals with strategic and detailed procedural issues * Helps minimise risk by explaining the correct procedures to follow * Shows how to identify potentially litigious situations * Incorporates wide-ranging recent legislation into its analysis